Building age, depreciation and real option value – an Australian case study - Costello, Gregory (Pacific Rim Real Estate Society Conference, 2012)
This paper examines the influence of building age as a measure of depreciation and real option (redevelopment) value within a large Australian housing market. A number of authors have proposed that building age used as an independent variable in hedonic analysis of housing markets can proxy for other omitted variables. Recent research suggests that depreciation of structures, location influences and real option potential are all measured implicitly with building age if hedonic models are not correctly specified so as to effectively identify and isolate the influence of these factors. The influence of building age in identifying and measuring the option value of redevelopment potential is tested empirically in a large Australian housing market (Perth, Western Australia). Specific housing submarkets are identified as having significant variance in building age of the housing stock. Transactions from these submarkets over the sample period 1995-2010 are analysed within several hedonic models to test these influences. Consistent with recent similar research in this area, an "intensity" variable is used. This variable is constructed from the ratio of building areas from sales of existing properties to building areas from sales of “new” construction within the same submarkets. The preliminary results confirm this variable as providing robust characteristics in identifying and measuring these influences.